Development of a Flipbook-based E-module integrated with GeoGebra and Genially on Similarity - Cholilah, Mulik; Noor Fatirul, Achmad; Harwanto (JTP - Jurnal Teknologi Pendidikan, 2024)
The aim of this research is to develop an e-module using flipbook media that is integrated with GeoGebra and Genially in Mathematics subjects, especially about similarity for class IX SMP Khadijah 2 Surabaya which can be used as interactive teaching material. The objective of this study is to develop an e-module using a flipbook for the Mathematics subject, specifically on the topic of similarity for Grade IX at SMP Khadijah 2 Surabaya, that is both effective and suitable for use. The research method employed is the R&D (Research & Development) model by Borg and Gall, which involves data collection to produce, develop, and validate the product, utilizing the ASSURE method introduced by Robert Heinich and colleagues in the 1980s. This study uses the ASSURE model, which consists of six steps: 1) Analyze Learner Characteristics; 2) State Performance Objectives; 3) Select Methods, Media, and Materials; 4) Utilize Materials; 5) Require Learner Participation; 6) Evaluate and Revise. The data used in this research includes both qualitative and quantitative data. The research data was obtained from the feasibility level assessed by learning media experts at 83%, design experts at 92%, learning material experts at 98%, peer trials at 100%, small group trials with 5 students at 88%, medium group trials with 9 students at 90%, and large group trials with 24 students at 86%.